Characterization of ciprofloxacin liposomes: derivative ultraviolet spectrophotometric determinations - (:unkn) unknown (TAYLOR & FRANCIS LTD, 1997)
Neutral, (-) and (+) charged CF encapsulated liposome formulations prepared with EPC:Chol and DPPC:Chol lipids were investigated for their loading capacity, encapsulation % and release properties. CF amounts in the liposomes were estimated using derivative UV spectroscopy. Among the liposome formulations DPPC:Chol and EPC:Chol neutral formulations had a significantly higher loading capacity and slowest release rate compared with (-) and (+) charged liposomes. The derivative UV spectroscopy was found to be an easy and sensitive method for direct estimation of CF in liposomes.
Keywords: ciprofloxacin; liposome entrapment; drug release; derivative spectrophotometry